Biofluid biomarkers for Alzheimer’s disease - Wang, Sensen; Xie, Sitan; Zheng, Qinpin; Zhang, Zhihui; Wang, Tian; Zhang, Guirong (Frontiers in Aging Neuroscience, 2024)
Alzheimer's disease (AD) is a multifactorial neurodegenerative disease, with a complex pathogenesis and an irreversible course. Therefore, the early diagnosis of AD is particularly important for the intervention, prevention, and treatment of the disease. Based on the different pathophysiological mechanisms of AD, the research progress of biofluid biomarkers are classified and reviewed. In the end, the challenges and perspectives of future research are proposed.